Designable Integration of Silicide Nanowire Springs as Ultra‐Compact and Stretchable Electronic Interconnections. Issue 6 (2nd December 2021) - Yuan, Rongrong; Qian, Wentao; Liu, Zongguang; Wang, Junzhuan; Xu, Jun; Chen, Kunji; Yu, Linwei
Abstract: Stretchable electronics are finding widespread applications in bio‐sensing, skin‐mimetic electronics, and flexible displays, where high‐density integration of elastic and durable interconnections is a key capability. Instead of forming a randomly crossed nanowire (NW) network, here, a large‐scale and precise integration of highly conductive nickel silicide nanospring (SiNi x ‐NS) arrays are demonstrated, which are fabricated out of an in‐plane solid–liquid–solid guided growth of planar Si nanowires (SiNWs), and subsequent alloy‐forming process that boosts the channel conductivity over 4 orders of magnitude (to 2 × 10 4 S cm −1 ). Thanks to the narrow diameter of the serpentine SiNi x ‐NS channels, the elastic geometry engineering can be accomplished within a very short interconnection distance (down to ≈3 µm), which is crucial for integrating high‐density displays or logic units in a rigid‐island and elastic‐interconnection configuration. Deployed over soft polydimethylsiloxane thin film substrate, the SiNi x ‐NS array demonstrates an excellent stretchability that can sustain up to 50% stretching and for 10 000 cycles (at 15%). This approach paves the way to integrate high‐density inorganic electronics and interconnections for high‐performance health monitoring, displays, and on‐skin electronic applications, based on the mature and rather reliable Si thin film technology. Abstract : A large‐scale integration of highly conductive (>2 × 10 4 S cm −1 ) nickel silicide nanospring arrays, fabricated out of a guided growth of planar silicon nanowires and alloy‐forming process, is demonstrated, with narrow diameter <160 nm and elastic design that can sustain up to 50% stretching and for 10 000 cycles (at 15%). It is ideal for interconnecting high‐density displays or logic units on elastomer substrates.